2014
DOI: 10.4067/s0718-58392014000300003
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performances of three vetch species growing under different drought levels

Abstract: The current challenge of agriculture is to get the best yields while overcoming frequent water deficit conditions. The objective of this study was to compare performances of three vetch species (Vicia narbonensis L., V. sativa L., and V. villosa Roth) subjected to water stress. Plants were sown in pots under rainout shelter and submitted to four water regimes: control (100% field capacity [FC]), 80%, 60%, and 40% FC through 3 yr experiment. Results showed that V. narbonensis had the smallest declines in all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Another study was conducted by Sareen et al (2014) in India, who analyzed the interaction between genotype and environment in wheat landraces treated under two abiotic stresses (drought and heat) and found a good correlation between MP and TI (tolerance index) as well as between SI and TOL. Haffani et al (2014) in Tunisia measured the effect of four water regimes in terms of field capacity (100% FC, 80% FC, 60% FC, and 40% FC) on the agronomic performance of three vetch species. They found that the STI is proportional to the applied water regime, and DM is affected by the level of water stress in the three years of the experiment.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Another study was conducted by Sareen et al (2014) in India, who analyzed the interaction between genotype and environment in wheat landraces treated under two abiotic stresses (drought and heat) and found a good correlation between MP and TI (tolerance index) as well as between SI and TOL. Haffani et al (2014) in Tunisia measured the effect of four water regimes in terms of field capacity (100% FC, 80% FC, 60% FC, and 40% FC) on the agronomic performance of three vetch species. They found that the STI is proportional to the applied water regime, and DM is affected by the level of water stress in the three years of the experiment.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Traditionally in Spain, it is marginally produced in Castilla La Mancha, Extremadura, and Andalucía [20]. It grows on neutral/alkaline soils with low to medium rainfall conditions, and is adapted to both hot and cold temperatures [20][21][22][23]. Its production can vary between 470 kg/ha in poor conditions to 4000 kg/ha on deep and fertile soils with more abundant water provision or rainfall [20].…”
Section: An Overview Of Narbon Vetch In Animal Nutritionmentioning
confidence: 99%